Magnesium content in soil and roughages depending on soil type and forage crops - Jakšić Snežana P.; Vučković Savo M.; Vasin Jovica R.; Ninkov Jordana M.; Dozet Gordana K.; Živanov Milorad S.; Banjac Dušana D. (Journal of Agricultural Sciences (Belgrade), 2017)
The aim of this study is to examine the effects of soil type and forage crops on the content of magnesium in soil and roughages, as well as forage quality regarding Mg content for the prevention of animal disease ‘tetany’. The trial was carried out on chernozem and humogley under alfalfa and red clover. Samples for determination of Mg content in plant and total Mg content in soil were digested using the apparatus Milestone Ethos 1. The content of Mg was determined using the apparatus ICP-OES Vista Pro-Axial Varian. The average total Mg content in soil of the tested sites was 0.64%. Total Mg content in chernozem was higher than in humogley. A higher total Mg content was in the deeper horizon. A significant positive correlation was found between total Mg content in soil and soil pH as well as the content of CaCO3. The average Mg content in forage crops was 0.28%. A higher Mg content in the dry matter was observed in crops grown on humogley. Mg content was significantly higher in red clover. There was no risk for the occurrence of animal disease ‘tetany’ regarding Mg content in crops, because the ratio K/(Ca+Mg) was below 2.2, and K and Mg content in the dry matter of crops was below the critical value. [Project of the Serbian Ministry of Education, Science and Technological Development, Grant no. TR31072: Stanje, tendencije i mogućnosti povećanja plodnosti poljoprivrednog zemljišta u Vojvodini]